METHODOLOGY OF LEARNING ENGLISH (Archive of Conferences, 2020)
Though this article, you can gain some knowledge and skills on how to learn foreign languages effectively, especially English, using what methods and approaches. The purpose of the article is to review the methods and techniques of the modern education.